IMPLEMENTASI KEBIJAKAN PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH - Maulana, Rizal Fatli; Darmojo, Hardjito S.; Muzakir, Athar Ismail (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
The purpose of this study is to analyze the implementation of school operational assistance fund management policies (a study at SDN Buaranjati 1). This study employed a qualitative approach. Data collection techniques included observation, documentation, and interviews with informants to complete the research. The theory used in this study is Edward III's theory related to policy implementation and development, focusing on communication indicators (transmission, clarity, and consistency), resources (human resources, operational budget, facilities, and authority), disposition (commitment and responsibility), and bureaucratic structure (procedures and bureaucratic order). The results of this study indicate that in the first sub-indicator, communication, namely transmission, is not optimal, while in the clarity sub-indicator, it has been running well, and consistency has not been optimal. In the second sub-indicator, resources, namely human resources, operational budget, and facilities, are still not fully maximized, while authority has been running well. In the third sub-indicator, disposition, namely commitment and responsibility, has been running effectively. Finally, regarding the bureaucratic structure, procedures have been running well, while hierarchical order has not been optimal. Supporting factors include optimal outreach from the school, effective coordination between the committee and the school, and optimal support from teachers through their skills, insights, and motivation in improving educational quality. Inhibiting factors include annual changes in technical guidelines, delays in reporting BOS funds, and disparities between budget planning and realization. Keywords: Implementation, Policy, Management